Pengembangan E-Modul IPA Berbasis Pendekatan Saintifik Menggunakan Canva dan Flip PDF Profesional - Sri Wulandari; Zulirfan Zulirfan; Zulkan Zulkan (Educatio, 2023)
This research was conducted with the aim of knowing the feasibility of developing science e-modules based on a scientific approach using a combination of the Canva Application and Flip PDF Professional. The research method used is using the ADDIE model research and development (Research & Development/R&D) design and approach. The research instrument used was an e-module validation questionnaire by material experts, media and science learning experts as well as teacher and student practicality questionnaires. The IPA e-module using a combination of Canva and Flip PDF Professional has been successfully developed by integrating aspects of the scientific approach in the e-module learning flow. The expert validation results obtained an average score of 3.57 with a very valid category. The results of the practicality test for teachers and students obtained an average score of 3.75 and 3.89 respectively, so that the e-module practicality category is in the very practical category. Based on the results of the validation and practicality tests, it can be stated that the e-module is feasible and easy to use for science learning purposes for grade VIII students of SMP/MTs.